1997
DOI: 10.1002/(sici)1098-2795(199709)48:1<9::aid-mrd2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of in-vitro-produced bovine blastocysts after vitrification, in-straw direct rehydration, and culture

Abstract: Morphological signs of injury and regeneration following vitrification and warming of bovine embryos were studied by light and electron microscopy. In‐vitro‐produced Day 7 expanded blastocysts (Day 0 = day of insemination) were vitrified by a two‐step equilibration method using ethylene glycol and dimethyl sulphoxide as cryoprotectants. Thawing was performed by in‐straw direct rehydration, followed by in vitro culture on a granulosa cell monolayer. Embryos were processed for transmission electron microscopy im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 15 publications
4
9
0
1
Order By: Relevance
“…Embryo exposure of embryos to cryoprotectants can have indirect consequences, such as causing biochemical injuries that can result from specific interactions between the cryoprotectant and proteins, lipids, or DNA, modifying the transport systems (Uechi et al, 1997) and the ability of embryo to regulate pH (Lane et al, 2000), with consequences to the metabolism perturbations (Somero, 1986), the Krebs cycle, and Embden-Meyerhof pathway activity (Rieger et al, 1991) and the glucose uptake and lactate production (Gardner et al, 2001). Our experiments supported previous reports (Vajta et al, 1997;Kaidi et al, 1999), which described the reversibility of injuries induced by vitrification in a few hours after warming. However, the abnormal quantitative secretion of protein observed for vitrified/thawed blastocysts during 18-24 hr of culture after warming indicates that this process is not well restored at this time, probably due to an alteration of synthetic-secretory mechanisms of the embryonic cells that are completely restored only after 29-35 hr of postthawing culture.…”
Section: Discussionsupporting
confidence: 88%
“…Embryo exposure of embryos to cryoprotectants can have indirect consequences, such as causing biochemical injuries that can result from specific interactions between the cryoprotectant and proteins, lipids, or DNA, modifying the transport systems (Uechi et al, 1997) and the ability of embryo to regulate pH (Lane et al, 2000), with consequences to the metabolism perturbations (Somero, 1986), the Krebs cycle, and Embden-Meyerhof pathway activity (Rieger et al, 1991) and the glucose uptake and lactate production (Gardner et al, 2001). Our experiments supported previous reports (Vajta et al, 1997;Kaidi et al, 1999), which described the reversibility of injuries induced by vitrification in a few hours after warming. However, the abnormal quantitative secretion of protein observed for vitrified/thawed blastocysts during 18-24 hr of culture after warming indicates that this process is not well restored at this time, probably due to an alteration of synthetic-secretory mechanisms of the embryonic cells that are completely restored only after 29-35 hr of postthawing culture.…”
Section: Discussionsupporting
confidence: 88%
“…We can hypothesize that the need of replacement of high amount of extruded and dead cells forced vitrified blastocysts to increase their mitotic activity. As shown in previous studies, the morphology of bovine in vitro produced and vitrified embryos after 24 hr culture was also normalized, except for similarly persistent increased amount of cellular debris in PvS (Vajta et al, 1997). In both porcine and bovine embryos, junctional contacts between TB cells were restored, a blastocoele was formed, and mitochondrial morphology was to some degree normalized.…”
Section: Discussionsupporting
confidence: 79%
“…The mitochondria in general as well as other organelles and cells of such embryos react by either distension or shrinkage, which in the case of whole cells (at least of a proportion of them) results in degeneration. Some of these degenerated cells are extruded (Vajta et al, 1997). Our experiments also proved the damage of degenerated cells on the biochemical level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, fetal losses of up to 30% have been observed before term (Thompson et al, 1998). Vajta et al (1997b) observed serious subcellular injuries in vitri®ed bovine blastocysts when viewed by electron microscopy but this damage was progressively repaired over a 24-hour period. Although it is speculative that damage to intracellular organelles of donor cells is not consequential in cloning, because the recipient ooplasm provides all the necessary cytoplasmic components, the mere occurrence of such damage might suggest the possibility of more serious, chromosomal damage affecting the function of the cloned nucleus.…”
Section: Discussionmentioning
confidence: 99%